SMALL AND MEDIUM ENTERPRISE DEVELOPMENT STRATEGY: SWOT-BALANCED SCORECARD PERSPECTIVE - Novie Susanti Suseno; Marti Dewi Ungkari; Rafael Gani Barlian (Kajian Akuntansi, 2023)
This study aims to find out what strategy should be used by UKM Rai SJ Leather by using SWOT analysis, where the Balanced Scorecard is used as the basis for strategy formulation. Informants were selected based on the consideration that the person was considered to know the most about various information related to the company's operational strategy. In this study, the authors use primary data and secondary data. The research method used is a qualitative method. Data collection techniques using library research, interviews, and internet studies. The data analysis technique was carried out by means of data reduction, data presentation, and verification. The results showed that after weighting using the IFAS matrix with a value of 1.95 and the EFAS matrix with a value of -0.5, the Rai SJ Leather SME is located in quadrant two. The strategy that must be used in quadrant two is concentric diversification by utilizing strengths to overcome various threats. The strategy from the growth and learning perspective is that SMEs must recruit human resources who have knowledge and abilities in the field of technology and quality control; in the internal business process perspective, the strategy that must be carried out is to make new innovations, the strategy from the customer perspective is to increase the brand to be recognized more widely, the strategy on a financial perspective is to increase revenue. Keywords: Balanced Scorecard, Business Strategy, SWOT Analysis.